Seroprevalence of highly pathogenic avian influenza H5 subtype clade 2.3.2 on ducks and muscouvy ducks in small holders farm - Martindah, Eny; Indriani, Risa; Wahyuwardani, S (Indonesian Journal of Animal and Veterinary Sciences, 2014)
Seroprevalence studies of HPAI H5 subtype in ducks and muscouvy duck in smallholders farm was carried out in Serang and Tangerang District, Banten Province. The study comprised a serological survey to define the distribution and prevalence of HPAI H5 subtype infection on ducks and muscouvy ducks as well as attempted isolation of the virus from these species. Unit of sample in each stage was randomly choosen by multy stage random sample. Blood samples were taken from ducks and muscouvy ducks that had never been vaccinated, purposively. Sera were tested using Haemaglutination Inhibition Test, antigen H5N1 (clade 2.3.2), while the cloaca and trachea swab samples was injected into specific pathogens free (SPF) embryonated 9-11 days old, to isolate the virus. Results showed that H5 subtype virus could be isolated from tracheal swabs of ducks in the various age groups. The seroprevalence of H5 subtype virus in Banten Province was 25.5%, in which, 24.3% occured in ducks and in muscouvy duck in the rate of 1.2%, with titer HI positive was > 3log2. Based on species, seroprevalence level HPAI H5 subtype in ducks was 3-4 times higher than the level of seroprevalence of HPAI H5 subtype in muscouvy duck, which indicated that the H5 subtype virus more likely to circulate in the ducks flock than in muscouvy duck. This study noted that both muscouvy duck and ducks appeared to play a significant role in the epidemiology of the disease. Key Words: Seroprevalence, Ducks, Muscouvy Duck, HPAI H5 Subtype